2016
DOI: 10.21037/atm.2016.03.54
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation and lung cancer screening

Abstract: Smoking behavior may have a substantial influence on the overall effect of lung cancer screening. Non-randomized studies of smoking behavior during screening have indicated that computer tomography (CT) screening induces smoking cessation. Randomized studies have further elaborated that this effect has to do with participation in screening alone and not dependent on the CT scan. Participants in both CT and control arm in randomized screening trials had higher smoking abstinence rate compared to that of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…People who undergo a discussion about lung cancer screening are expected to have a stronger motivation to quit smoking, and the discussion process is a unique opportunity to engage current smokers in modifying their smoking behavior. However, many studies demonstrated the receipt of lung cancer screening is not strongly linked to smoking cessation (19). Our study showed the physician-patient discussion was not associated with any smoking behavior change, neither considering quitting smoking in the next 6 months nor stopping smoking for one day or longer in the past year.…”
Section: Discussionmentioning
confidence: 49%
“…People who undergo a discussion about lung cancer screening are expected to have a stronger motivation to quit smoking, and the discussion process is a unique opportunity to engage current smokers in modifying their smoking behavior. However, many studies demonstrated the receipt of lung cancer screening is not strongly linked to smoking cessation (19). Our study showed the physician-patient discussion was not associated with any smoking behavior change, neither considering quitting smoking in the next 6 months nor stopping smoking for one day or longer in the past year.…”
Section: Discussionmentioning
confidence: 49%
“…Neither trial demonstrated a difference in smoking cessation between the screening group and the control group. However, there is some evidence that a positive screening test result increases the smoking cessation rate 11. Our own data from the Cosmos-II trial (CT lung cancer screening in Italian population) support this 9.…”
mentioning
confidence: 58%
“…Previous data10 have suggested that taking part in lung screening may provide reassurance to the subject and providing a ‘licence to smoke’, in particular, for smokers who receive favourable screening results. Indeed, one possible drawback of lung cancer screening may be that it can induce a false sense of safety and security in the participants so that they may feel protected against the harmful effect of smoking 11. Thus, a normal CT scan result may reduce the motivation of a smoker to quit and inadvertently encourage continued smoking.…”
mentioning
confidence: 99%
“…Two recent systematic reviews showed that undergoing LDCT screening in itself is not sufficient to achieve long-term smoking abstinence (27, 28). On one hand, however, there is some evidence that positive LDCT screening results (e.g., detection of nodules) are associated with increases in quit rates and in reducing relapse among recent quitters (23, 24, 27, 29).…”
Section: Resultsmentioning
confidence: 99%